2002
DOI: 10.1379/1466-1268(2002)007<0191:thsrac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

&cestchinlong;The heat shock response and cytoprotection of the intestinal epithelium

Abstract: Following heat stress, the mammalian intestinal epithelial cells respond by producing heat shock proteins that confer protection under stressful conditions, which would otherwise lead to cell damage or death. Some of the noxious processes against which the heat shock response protects cells include heat stress, infection, and inflammation. The mechanisms of heat shock response-induced cytoprotection involve inhibition of proinflammatory cytokine production and induction of cellular proliferation for restitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 61 publications
1
72
0
Order By: Relevance
“…This response is specific to the bacteria and their SCS since the MRS broth or variations in pH could not induce the Hsp70 expression. Because the production of Hsp70 is a protective response (Malago et al, 2002;Ovelgönne et al, 2000), we suggest that one mechanism for the beneficial attributes of the non-starter lactobacilli is the ability to induce the expression of Hsp70 by the bacteria and their antimicrobial products. The induced Hsp70 could function in the stabilisation of the cytoskeleton of intestinal epithelial cells after being distorted during adhesion and invasion by Salmonella (Jepson et al, 1995(Jepson et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This response is specific to the bacteria and their SCS since the MRS broth or variations in pH could not induce the Hsp70 expression. Because the production of Hsp70 is a protective response (Malago et al, 2002;Ovelgönne et al, 2000), we suggest that one mechanism for the beneficial attributes of the non-starter lactobacilli is the ability to induce the expression of Hsp70 by the bacteria and their antimicrobial products. The induced Hsp70 could function in the stabilisation of the cytoskeleton of intestinal epithelial cells after being distorted during adhesion and invasion by Salmonella (Jepson et al, 1995(Jepson et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Further, when administered intravenously, lactobacilli cultivation products induce the expression of a putative protective protein (Hsp70) in the rat heart that subsequently protects the heart against ischaemia and reperfusion tachyarrhythmia (Oxman et al, 2000). Since heat shock proteins suppress the synthesis of inflammatory cytokines like IL-8 (Malago et al, 2002) and lactobacilli induce these proteins in the rat heart, it is reasonable to suggest that lactobacilli also exert a beneficial effect upon the gut following oral uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chemoattractant is produced following activation of the transcription factor, nuclear factor kappa B (NF-κB) (Malago et al, 2002). DSS can activate this factor and could in turn lead to synthesis and secretion of IL-8 (Marrero et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since polymorphonuclear neutrophil infiltration is the primary and central lesion of colitis and is usually followed by loss of the epithelium, loss of goblet cells and crypt damage (Iba et al, 2003), it follows that the observed SA protection against colitis in this study could be mediated via its ability to inhibit the polymorphonuclear neutrophil infiltration and the subsequent pathology. SA is well known to mediate most of its effects via activation of the heat shock response that, in turn, suppresses the inflammatory response (Malago et al, 2002). The dose of SA used in this study (10 mg/kg, intraperitoneally, every 48 h) had a broad safety margin, as none of the rats died or showed abnormal behavior due to SA.…”
Section: Discussionmentioning
confidence: 99%